P77 Predictors of good clinical outcome after thrombectomy for distal medium vessel occlusions. (29th August 2022) - Guenego, A; Lubicz, B
Abstract : Introduction: Good clinical outcome predictors have been emphasized in mechanical thrombectomy (MT) foracute ischemic stroke (AIS) withlarge vessel occlusion (LVO). MT for distal, medium vessel occlusions (DMVO) is still debated. Aim of study: We sought to assess the factors associated with clinical outcome after MT for DMVO. Methods: We retrospectively analyzed the data of consecutive patients who underwent MT for a primary DMVO in one large academic centerand aimed to identify the baseline clinical, imaging and MT factors associated with good clinical outcome (defined as modified Rankin scale [mRS] of 0–2) at 3 months. Results: Between January 2018 and January 2021, 61 patients underwent a MT for an AIS with a primary DMVO. Overall, good clinical outcome was achieved in 56% (34/61) of our patients. In multivariate analysis, we identified higher age (ODDS ratio 0.89 [0.83–0.96], p=0.003), puncture to recanalization time (ODDS ratio 0.97 [0.93–0.99], p=0.033), and baseline core volume (ODDS ratio 0.84 [0.75–0.94], p=0.003) as negative predictors of good clinical outcome, while final complete (or near-) recanalization (mTICI 2c-3) was a predictor of good outcome (ODDS ratio 14.19 [1.99–101.4], p=0.008). Conclusion: An older age, a longer puncture to recanalization time and a higher baseline core volume were strongly associated with poor clinical outcomes, while successful recanalization (mTICI 2c-3) was associated with better outcomes after MT for DMVO. References: Guenego A, Mine B, Bonnet T, et al . Thrombectomy for distal medium vessel occlusion with a new generation of stentretriever (tigertriever 13). Interv Neuroradiol 2021: 15910199211039926. 2021/09/14. DOI: 10.1177/15910199211039926. Do you have any conflict of interest to declare? : Yes Conflict of Interest Statement: Consultancy for Rapid Medical (travel grant only)